Motivasi belajar Pengaruh Motivasi Berprestasi terhadap Prestasi Belajar Siswa pada Mata Pelajaran Ekonomi - Desi Patulak Desi Patulak (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX - Sulawesi, 2019)
This study aims to analyze the effect of achievement motivation on student achievement in economic subjects at SMK Imannuel Smart Rantepao, Toraja Utara Regency. In this study, the population was all 147 students of Imannuel Smart Rantepao, Toraja Utara Regency. Sampling in this study was taken by simple random sampling from each class that is 50% of the total population of 74 people. Analysis of the data in this study is multiple linear regression. The results of this study indicate that achievement motivation has a positive and significant effect of 0.217 on student achievement in economic subjects at SMK Imannuel Smart Rantepao, Toraja Utara Regency